Gestão de redes de cooperação entre bibliotecas: análise dos casos REDARTE/RJ E CBIES/RJ - Aragon, Cláudia (2017)
The present research aimed to investigate the management of networks of cooperation between libraries, based on the case study of the Rede de Bibliotecas e Centros de Informação em Arte no Rio de Janeiro (REDARTE/RJ) and the Compartilhamento de Bibliotecas de Ensino Superior do Estado do Rio de Janeiro (CBIES/RJ), to describe and analyze the management process; the reasons why a library participates in a cooperation network; how interaction and cooperation between members occurs; the determinants of network success and challenges; the contribution of the network to innovation in member libraries and the expectations for the future in the networks studied. According to the theoretical basis, analysis of the documentation produced by the networks and semi-structured interviews, we sought to understand how networks of libraries can be resilient in time. The results of the research led to the following evidences: a) the networks of libraries close to the community/society they serve are time-resilient; b) libraries supported politically and financially by the institutions to which libraries belong are time-resilient.